2009
DOI: 10.1103/physreva.80.063615
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable microchip ring trap for cold atoms and molecules

Abstract: We describe the design and function of a circular magnetic waveguide produced from wires on a microchip for atom interferometry using deBroglie waves. The guide is a two-dimensional magnetic minimum for trapping weak-field seeking states of atoms or molecules with a magnetic dipole moment. The design consists of seven circular wires sharing a common radius. We describe the design, the time-dependent currents of the wires and show that it is possible to form a circular waveguide with adjustable height and gradi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…It has been observed that filling the notch of a RDS stabilises against the snake instability [21], a result we explain in this Letter. Specifically, ring traps [22][23][24][25] might stabilise the ring dark soliton, but we show that their effect is in fact the opposite.In this Letter we consider the stability of the RDS in cylindrically symmetric confinement, showing that it is stable as long as the symmetry in the θ-direction is maintained. We show that the type of the simulation grid plays an important role related to the induced breaking of this symmetry.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…It has been observed that filling the notch of a RDS stabilises against the snake instability [21], a result we explain in this Letter. Specifically, ring traps [22][23][24][25] might stabilise the ring dark soliton, but we show that their effect is in fact the opposite.In this Letter we consider the stability of the RDS in cylindrically symmetric confinement, showing that it is stable as long as the symmetry in the θ-direction is maintained. We show that the type of the simulation grid plays an important role related to the induced breaking of this symmetry.…”
mentioning
confidence: 80%
“…It has been observed that filling the notch of a RDS stabilises against the snake instability [21], a result we explain in this Letter. Specifically, ring traps [22][23][24][25] might stabilise the ring dark soliton, but we show that their effect is in fact the opposite.…”
mentioning
confidence: 80%
“…There are several ways to produce a toroidal trap for atom condensates [27,[33][34][35][36]. In the case of finite quantum rings made of the Q1D lattices considered, we induce an effective magnetic flux through the ring in order to induce a current.…”
Section: Persistent Currentsmentioning
confidence: 99%
“…Pure static fields 20 or light fields 21,22 have also been used. However, practical atom chip schemes for interferometry with a wide dynamic range and versatile geometries are still very much sought after [23][24][25][26][27][28] . Such schemes may enable, for example, sensitive probing of classical or quantum properties of solid-state nanoscale devices and surface physics (for example, refs [29][30][31][32][33].…”
mentioning
confidence: 99%
“…This is expected to enhance considerably the power of non-interferometric measurements with ultracold atoms on a chip, which have already contributed, for example, to the study of long-range order of current fluctuations in thin films 34 , the Casimir-Polder force [35][36][37][38] and Johnson noise from a surface 39 . In addition, interferometry integrated on a chip is a crucial step towards the development of miniature rotation, acceleration and gravitational sensors based on guided matter waves 23,27 .…”
mentioning
confidence: 99%